Physics and Philosophy of Wave Reference Framesin a Retrospective of 20-th Century Findings and Illusions (Global Journal of Science Frontier Research, 2017)
Abstract not found
Keywords: aurora effect; comprehension horizon; inertial reference frame; relativity; SMA; wave reference frame